(untitled) (Entrepreneurship Journal for Finance and Business, 2026)
The research aims to measure the impact of public budget indicators and institutional quality (the quality of governing institutions in the economy) in reducing public debt for a selected group of Arab countries with renter economies for the period (2002-2023). Two standard models have been built to achieve this goal: The first model focused on measuring the impact of the general budget through its basic indicators represented by public spending and public revenues expressed in tax revenues, with the introduction of the oil price variable as a control variable due to its fundamental importance in explaining the dynamics of public debt in oil economies. The second model focused on measuring the impact of the six institutional quality indicators issued by the World Bank (control of corruption, political stability, government effectiveness, rule of law, voice and issue, and regulatory quality) on public debt. Using static analysis of longitudinal data models represented by its three models (pooled regression model, fixed effects model, and random effects model) for eight Arab oil countries, the research reached a set of results: For general budget indicators, the results showed that reducing public spending can contribute to reducing public debt, while there was no significant effect of oil revenues. While for oil prices, they had an impact in reducing public debt. As for institutional quality indicators, the results showed the impact of (political stability, government effectiveness, voice and issue) on reducing public debt, while the results showed that (control of corruption, rule of law, and regulatory quality) contribute to the accumulation of public debt. Therefore, the results of this research confirm the importance of the financial budget and institutional quality in reducing public debt and its sustainability in the long run.